2021
DOI: 10.35848/1347-4065/abdb83
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and inelastic X-ray scattering measurements on SiGeSn polycrystalline alloy

Abstract: The impact of Sn on Si1-xGex through its thermal conductivity and phonon properties was investigated to develop an attractive material for thermoelectric devices. The Si-rich polycrystalline Si1-x-yGexSny alloy was synthesized by ball-milling technique. The as-synthesized alloy had substitutional Sn content of 1.60%, which it maintained as high as 0.54% after sintering at 1000 °C. The thermal conductivity was found to be reduced by the introduction of this tiny amount of Sn. Inelastic X-ray scattering measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…We previously reported the poly-Si 1-x-y Ge x Sn y synthesized by using the ball milling method, and that the introduction of Sn into Si 1-x Ge x successfully reduces the thermal conductivity. 24) However, the substitutional Sn content achieved in the poly-Si 1-x-y Ge x Sn y was only 0.54% because the synthesized polycrystalline powder was necessary to be sintered into pellets under high pressure at high temperature as high as 1000 °C. On the other hand, we also reported Sn nanodots (Sn-ND), which were formed on the Si substrate covered by the thermally oxidized SiO 2 layer, mediated formation of the poly-Ge 1-x Sn x layer at low temperature achieving high Sn content exceeding its solubility limit in Ge.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the poly-Si 1-x-y Ge x Sn y synthesized by using the ball milling method, and that the introduction of Sn into Si 1-x Ge x successfully reduces the thermal conductivity. 24) However, the substitutional Sn content achieved in the poly-Si 1-x-y Ge x Sn y was only 0.54% because the synthesized polycrystalline powder was necessary to be sintered into pellets under high pressure at high temperature as high as 1000 °C. On the other hand, we also reported Sn nanodots (Sn-ND), which were formed on the Si substrate covered by the thermally oxidized SiO 2 layer, mediated formation of the poly-Ge 1-x Sn x layer at low temperature achieving high Sn content exceeding its solubility limit in Ge.…”
Section: Introductionmentioning
confidence: 99%
“…This study focused especially on reducing the thermal conductivity by the enhancement of phonon scattering. [8][9][10][11] Polycrystalline materials with a grain size larger than the mean free path of an electron and smaller than that of a phonon are effective in reducing the thermal conductivity. Therefore, poly-Si is expected to be a thermoelectric material.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the thermal conductivity of polycrystalline Si 1−x Ge x can be further reduced by introducing Sn atoms, whose mass is 4.2 times greater than that of Si and 1.6 times greater than that of Ge, into the lattice substitution positions. 9,10) Similar to the introduction of Ge into Si, it is theoretically predicted that the substitution of Sn atoms into Si 1−x Ge x will result in lower thermal conductivity compared to Si 1−x Ge x . 18) This theoretical calculation shows that the introduction of Sn as well as a certain high Si content is necessary to reduce the thermal conductivity practically as the solid solubility limits of Sn in Ge and Si are very low.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these applications, the Ge 1−x−y Si x Sn y is also expected to be used as a thermoelectric material 15,16) because it theoretically possesses a low thermal conductivity. 17,18) Highperformance thin-film thermoelectric devices, 19,20) e.g.…”
Section: Introductionmentioning
confidence: 99%